European social model and challenges of globalization: searching the ways of balancing of the needs of the economy and societ - N.P. Topishko (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2015)
The features of the fundamental models of social policy in the EU and social procection system as one of its mechanisms has been characterized. The changes in the division of responsibility between the subjects of social partnership in providing social protection is analyzed. Special attention paid to the increasing socio-economic contradictions in terms of global transformations and social orientation of stabilization measures by governments. The principles on which reform is carried taxation and social welfare systems is observed. It is also described the change in the tax system in terms of finding ways to fiscal consolidation, including the measures of increasing rate of progressivity of the tax system and fiscal role of indirect taxes, broadening the tax base, increase the tax burden on passive income. Approaches to adopt the European model of social protection to globalization and the rise of the economic crisis has been investigated. The ways to achieve a balance between the social functions of the state and the level of financial supportis outlined.